Aves frugívoras na porção extremo-oeste da Floresta Atlântica, Brasil : composição específica, características e sensibilidade à fragmentação florestal. - Mendonça, Luciana Baza (2009)
Frugivorous birds are one of the most representative groups in Neotropical bird communities. They are important drivers of ecological functions regarded as key processes of biodiversity maintenance in biotic communities, and can play an important role in forest regeneration. Nevertheless, as a consequence of processes as habitat loss and overhunting, frugivorous birds are also one of the most threatened bird groups in the Brazilian Atlantic Forest. The present study, divided in two chapters, address two subjects relevant to conservation of frugivorous birds: spatial distribution and sensitivity to forest fragmentation, taking place in the Upper Paraná River, the study site. The region lies between the states of Paraná and Mato Grosso do Sul (Brasil), at a transition zone between two world's biodiversity hotspots and areas of conservation priority: the Brazilian Atlantic Forest, and the Cerrado (Brazilian savanna). In the first chapter, we investigated species composition and ecological traits of the frugivorous bird assemblage at the Upper Paraná River, regarding its similarity to the biomes Atlantic forest, Cerrado, Pantanal and Chaco. In the second, we analyzed sensitivity of frugivorous birds to forest fragmentation, providing helpful information to identify species of greater conservation concern.